Laser-assisted synthesis of two-dimensional transition metal dichalcogenides: a mini review - Wang, Hanxin; Xu, Manzhang; Ji, Hongjia; He, Tong; Li, Weiwei; Zheng, Lu; Wang, Xuewen (Frontiers in Chemistry, 2023)
The atomically thin two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted the researcher’s interest in the field of flexible electronics due to their high mobility, tunable bandgaps, and mechanical flexibility. As an emerging technique, laser-assisted direct writing has been used for the synthesis of TMDCs due to its extremely high preparation accuracy, rich light–matter interaction mechanism, dynamic properties, fast preparation speed, and minimal thermal effects. Currently, this technology has been focused on the synthesis of 2D graphene, while there are few literatures that summarize the progress in direct laser writing technology in the synthesis of 2D TMDCs. Therefore, in this mini-review, the synthetic strategies of applying laser to the fabrication of 2D TMDCs have been briefly summarized and discussed, which are divided into top-down and bottom-up methods. The detailed fabrication steps, main characteristics, and mechanism of both methods are discussed. Finally, prospects and further opportunities in the booming field of laser-assisted synthesis of 2D TMDCs are addressed.